UMP research exploited waste sludge to make ‘S-Brick’ - UMP, PNC (Pejabat Naib Canselor, 2016)
A team of Universiti Malaysia Pahang (UMP) researchers had successfully produced bricks that were made of waste sludge and egg shells named S-Brick.